DESKRIPTIF KUANTITATIF DUKUNGAN SOSIAL PADA KEPALA SEKOLAH KELOMPOK BERMAIN (KB) DAN TAMAN KANAK-KANAK (TK) AISYIAH KABUPATEN GRESIK - Amelasasih, Prianggi (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2024)
Background: The many duties, roles and responsibilities of the school principal are in direct contact with teachers, school staff and the community around the school environment, so there is a need for social support from the parties concerned. The existence of this social support can make it easier for school principals to carry out all activities related to school services. Objective: This research aims to look at social support for school principals so that they can improve and maintain physical health and psychological well-being. This research measures a single variable, namely social support. Method: The research subjects were 71 principals of KB and Aisyiah Kindergarten schools in Gresik Regency. Data collection used a questionnaire with a Likert scale to measure the level of social support, consisting of 10 items. The data analysis technique used is descriptive statistics via the SPSS for Windows application. Result: Based on the results of the t test analysis, the difference in t value is 37,369 and the significance value between the mean value of the KB and TK levels in getting social support is p value 0.000 < 0.05. This shows that there is a significant difference between social support for KB and TK. With an empirical mean value for the KB level of 37.47 and an average empirical mean for the TK of 39.28. Conclusion: Level TK level has a greater empirical mean value than KB level, which shows that the TK school level has higher social support than KB school level